Student Self-Regulated in Remote Learning With the Implementation of Local Virtual Lab Based on Online Tutorial (LVL-BOT) - Palloan, Pariabti; Rahmadhanningsih, Sri; Viridi, Sparisoma; Jainuddin, Jainuddin; Swandi, Ahmad (Indonesian Review of Physics (IRiP), 2021)
This study aims to measure the level of Self-Regulated Learning (SRL), conceptual understanding and identify an increase in conceptual understanding after using LVL-BOT. This type of research is Pre-Experimental with One-Group Pretest-Posttest Design. The research sample consisted of 37 students from physics classes who took modern physics courses. Studentsâ€™ level of Self-Regulated Learning is administered using a questionnaire, and understanding of concepts is administered using a test. Based on the analysis results, the percentage level of Self-Regulated Learning is at a value of 87.7%, which is included in the very high category. There is a significant difference between the mean pre-test and post-test mean. The N-Gain Values of Photoelectric Effect and Black Body Radiation are 0.47 and 0.57, respectively. This shows an increase in studentâ€™s conceptual understanding, which is â€œenoughâ€ after using LVL-BOT.